2021
DOI: 10.1111/bcp.14721
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile and effects of mitotane in adrenocortical carcinoma

Abstract: Mitotane is the only adrenolytic drug approved by the Food and Drug Administration for treating adrenocortical carcinoma (ACC). This drug has cytotoxic effects on tumour tissues; it induces cell death and antisecretory effects on adrenal cells by inhibiting the synthesis of adrenocortical steroids, which are involved in the pathogenesis of ACC. However, high doses of mitotane are usually necessary to reach the therapeutic plasma concentration, which may result in several adverse effects. This suggests that imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 104 publications
0
41
0
1
Order By: Relevance
“…In this aspect, complete surgical resection with negative margins is an important prognostic factor [126]. If locally advanced or spread to distant sites, administration of the adrenolytic agent mitotane is usually recommended [128][129][130].…”
Section: Morphologic and Genomic Correlates Of Adrenal Cortical Carcinomamentioning
confidence: 99%
“…In this aspect, complete surgical resection with negative margins is an important prognostic factor [126]. If locally advanced or spread to distant sites, administration of the adrenolytic agent mitotane is usually recommended [128][129][130].…”
Section: Morphologic and Genomic Correlates Of Adrenal Cortical Carcinomamentioning
confidence: 99%
“…In the pool of hydrophobic drugs, mitotane, being a drug of choice for adrenocortical carcinoma (ACC) [7,8], also suffers from intrinsic poor aqueous solubility and low bioavailability [9,10]. Recently, Corso et al published a review which has provided a systematic details about the poor pharmacokinetics and pharmacodynamics of mitotane [11]. Contrarily, our article focuses more on the biopharmaceutics of mitotane with a special emphasis on development of new formulations and dosage forms.…”
Section: Introductionmentioning
confidence: 99%
“…Sixty years after the introduction of mitotane in the medical treatment of ACC, the whole spectrum of its pharmacological activities remains elusive. The main effect of mitotane in ACC is the induction of tumor cell death by apoptosis and/or necroptosis [ 39 ] and the on-target result of toxic disruption of adrenocortical steroidogenesis induced by mitotane remains the reduction of glucocorticoid excess, and other endocrine effects are considered off-target results. Among these, endocrine effects attributable to enhanced estrogen activity have been only partially studied, and the main conclusion of previous studies is that mitotane has an estrogenic effect that is ER-α dependent and mediated by mitotane-dependent increased hepatic SHBG synthesis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of crystal structures of complexes with agonist and antagonist molecules identified the helix 12 (H12, residues 532–552) as the most important structural element of each LBD monomer, acting as a molecular switch between the active and inactive conformation of the receptor with “flip-flop” mechanism [ 24 , 25 , 26 , 40 ]. After ligand interaction, the H12 helix undergoes a conformational change, assuming either an active conformation, where it is packed against helixes H3, H5/6, and H11 to close the binding site and create a surface essential for coactivators binding, or an inactive conformation, where it is displaced from the binding site and located in a groove formed by H3 and H5 [ 24 , 37 , 39 ]. As a consequence, the conformation of helix H12 can be used to assess the ability of a ligand to act as an agonist or antagonist in molecular dynamics simulations [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation